A study on organization policies and employee satisfaction at apmdc limited, mangampet, kadapa district - CHATLA, UMADEVI; NAGA, SILPA; POLI, RAJITHA (Journal of Management and Science, 2021)
An organization is basically association of human beings managing the human resources is the most important aspect for the organization. So, the organization policies and management decisions play an important role in organization to manage the human resources. The study conducted by the researchers involves organization policies and HR satisfaction in APMDCL Mangampet,Kadapa district. This study aims to measure the satisfaction level of employees towards organizational policies and to know what are the problems facing by them in organization and also identify the measures to solve the issues effectively. A sample of 90 employees are randomly selected and structured questionnaire employed for collecting responses from them. Simple percentage method used for analysis. Findings revealed that majority of the respondents over 65% of the employees are highly satisfied with the organization policies and 35% of the employees were not satisfied.